Heterogeneity between subgroups of first-line chemoimmunotherapy for extensive-stage small cell lung cancer patients: a meta-analysis and systematic review - Kang, Wenwen; Cheng, Jing; Pan, Luyun; Zhan, Ping; Liu, Hongbing; Lv, Tangfeng; Han, Hedong; Song, Yong (Frontiers in Oncology, 2024)
ObjectivesDifferences in clinicopathological characteristics of extensive-stage small cell lung cancer (ES-SCLC) patients may influence the immune response. This study aims to evaluate the heterogeneity of response to first-line chemoimmunotherapy between subgroups in ES-SCLC to screen out suitable populations.Materials and methodsWe searched the PubMed, EMBASE, and Cochrane Library databases from inception to December 3, 2022 for randomized controlled trials (RCTs) of ES-SCLC chemoimmunotherapy. We also reviewed main conferences from January 1, 2021 to October 1, 2023. A trial-specific hazard ratio (HR) ratio for each subgroup was calculated, and these ratios were then pooled using the deft approach.ResultsA total of 9 RCTs with 4099 patients were finally included. The pooled ratios were 0.92 (95% CI = 0.77 to 1.09) for OS-HRs and 0.79 (95% CI = 0.55 to 1.13) for PFS-HRs in women versus men. The pooled ratios of OS-HRs and PFS-HRs in patients with positive versus negative PD-L1 expression were 1.26 (95% CI = 0.91 to 1.73) and 1.08 (95% CI = 0.77 to 1.52), respectively. The pooled ratios of OS-HRs and PFS-HRs in patients without versus with brain metastasis were 0.77 (95% CI = 0.59 to 1.01) and 0.71 (95% CI = 0.44 to 1.12). No statistically significant differences were also found in terms of subgroups for age, liver metastasis, smoking status, ECOG PS, LDH level, type of platinum salt and race.ConclusionWomen or patients with negative PD-L1 expression or with LDH ≤ ULN or without brain metastasis tend to benefit more from first-line chemoimmunotherapy in ES-SCLC. More trials are needed to prospectively validate the therapeutic heterogeneity among clinicopathological characteristics.Systematic review registrationhttps://inplasy.com/inplasy-2023-3-0064/ identifier, INPLASY202330064.